Decision-Making Model of Product Modeling Big Data Design Scheme Based on Neural Network Optimized by Genetic Algorithm - Hu, Ming (Computational intelligence and neuroscience, 2021)
At present, machine learning artificial neural network technology, as one of the core technologies of enterprises, has received unprecedented attention. This technology is widely used in automatic driving, pattern recognition, teaching aid, product modeling, and other fields. According to the development of product design, this paper analyzes the factors that affect the decision-making of product design. The neural network optimized by genetic algorithm is studied, and the technical analysis of neural network algorithm before and after optimization is mainly carried out. The basic process of product modeling design model based on image processing under the background of big data is introduced. The multidirectional group decision-making model of product modeling design scheme in big data cloud environment is constructed. The final decision model can improve the overall design efficiency, shorten the manufacturing period, and provide a new idea for product modeling design.